Psoriasis - A Report of Disease Mimicry - Shalihin, Mohd Shaiful Ehsan; Abd Rahman , Mohd Aizuddin (IIUM Medical Journal Malaysia, 2020)
Introduction: Psoriasis is a chronic, noncontagious, multifactorial inflammatory skin condition that has several subtypes. Therefore, prior to actual diagnosis, it may mimics other similar illnesses. In acute condition, it typically presents with erythroderma macules associated with pain and itchiness rather than hypopigmented and numbness lesions that supposedly occurs in post-treatment or post-acute phase, rather than as initial presentation. Case report: We report a case of 18-year-old girl, who presented with nonspecific localized hypopigmented rash over her forehead and scalp associated with numbness for three weeks duration. She had no itchiness or rashes elsewhere. She had no history of atopy or recent exposure to new cosmetics. She had no joint pain or hair loss. She had no recent contact with anyone with similar lesion. No significant similar history among family members. Clinically, there is reduced in both soft touch and pin-prick sensation over affected areas. We refer this case to dermatologist with possibility of leprosy in view of her reduced sensation over the lesion. To our surprise, the skin biopsy revealed supportive points towards psoriasis. She responds well towards coal tar and topical corticosteroids-the first line treatment of psoriasis. Her numbness has also resolved. This case highlights that psoriasis do presents with localized numbness in which its diagnosis should be take into consideration before confining the disease towards leprosy only.